A response to article “Java sea Spirulina platensis chemical analysis and its protective ability against H2O2-exposed umbilical cord mesenchymal stem cells according to CD73, CD90, and CD105, viability, and HIF-1 alpha docking” - Ariyani Noviantari, Frans Dany, Putri Reno Intan (Journal of Applied Pharmaceutical Science, 2023)
This article does not have an abstract. Read the related article here: http://dx.doi.org/10.7324/JAPS.2022.120908